Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.expneurol.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Rodent neonatal germinal matrix hemorrhage mimics the human brain injury, neurological consequences, and post-hemorrhagic hydrocephalus

Abstract: Germinal matrix hemorrhage (GMH) is the most common neurological disease of premature newborns. GMH causes neurological sequelae such as cerebral palsy, post-hemorrhagic hydrocephalus, and mental retardation. Despite this, there is no standardized animal model of spontaneous GMH using newborn rats to depict the condition. We asked whether stereotactic injection of collagenase type VII (0.3 U) into the ganglionic eminence of neonatal rats would reproduce the acute brain injury, gliosis, hydrocephalus, periventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
113
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(122 citation statements)
references
References 79 publications
8
113
0
1
Order By: Relevance
“…S4). This finding differentiates our model as being more representative of low-grade GMH, i.e., Papile grades II and III in contrast with the grade IV haemorrhage modelled by previously published studies [24][25][26] . This finding further reinforces the need for this model of low-grade GMH and implies that the global impact of grade IV haemorrhage may mask the more subtle impact that GMH/IVH has on the NSPC within the SVZ.…”
Section: Moderate Gmh Causes Transient Early Impacts On Neonatal Devesupporting
confidence: 62%
See 3 more Smart Citations
“…S4). This finding differentiates our model as being more representative of low-grade GMH, i.e., Papile grades II and III in contrast with the grade IV haemorrhage modelled by previously published studies [24][25][26] . This finding further reinforces the need for this model of low-grade GMH and implies that the global impact of grade IV haemorrhage may mask the more subtle impact that GMH/IVH has on the NSPC within the SVZ.…”
Section: Moderate Gmh Causes Transient Early Impacts On Neonatal Devesupporting
confidence: 62%
“…Following IC blood injection at P0, we observed an increased number of falls [control ( n = 15), 4.5; sham ( n = 12), 9.33; and GMH ( n = 21), 22.23; ANOVA] and significantly more fails in grip strength testing [control ( n = 15), 1.875; sham ( n = 12), 1.83; and GMH ( n = 21), 2.47; ANO-VA] from P3 to P6; however, this difference did not persist and, contrary to published models of GMH (Aquilina et al [24] , Xue et al [26] , Lekic et al [25] ), we found no persistent deficits/alterations in neuromotor development up to Fig. S4).…”
Section: Moderate Gmh Causes Transient Early Impacts On Neonatal Devementioning
confidence: 63%
See 2 more Smart Citations
“…However, germinal matrix hemorrhage is common in premature infants, where it is a major cause of cerebral palsy. In a rodent neonatal germinal matrix hemorrhage model, Lekic et al 27 found that IVH resulted in an increase of thrombin and hydrocephalus. The role of thrombin and PAR-1 in hydrocephalus after neonatal IVH should be the subject of further investigation.…”
Section: Discussionmentioning
confidence: 99%